2014
DOI: 10.4103/0970-9185.137269
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of intravenous lidocaine on post-operative pain and acute rehabilitation after laparoscopic nephrectomy

Abstract: Background and Aims:Intravenous (I.V.) lidocaine has analgesic, antihyperalgesic and anti-inflammatory properties and is known to accelerate the return of bowel function after surgery. We evaluated the effects of I.V. lidocaine on pain management and acute rehabilitation protocol after laparoscopic nephrectomy.Materials and Methods:A total of 47 patients scheduled to undergo laparoscopic nephrectomy were included in a two-phase observational study where I.V. lidocaine (1.5 mg/kg/h) was introduced, in the secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 33 publications
1
36
0
2
Order By: Relevance
“…Target-controlled infusion of sufentanil (Gepts pharmacokinetic model) was used during anesthesia with sevoflurane to maintain the BIS value between 40 and 50. Intraoperative sufentanil consumption was similar for both groups (139 µg vs 121 µg), and no difference in time to tracheal extubation was noted [25]. Butterworth et al suggested inhibition of brain cell excitability as a mechanism for analgesia from infused lidocaine by increasing the current threshold of rat hippocampal pyramidal cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Target-controlled infusion of sufentanil (Gepts pharmacokinetic model) was used during anesthesia with sevoflurane to maintain the BIS value between 40 and 50. Intraoperative sufentanil consumption was similar for both groups (139 µg vs 121 µg), and no difference in time to tracheal extubation was noted [25]. Butterworth et al suggested inhibition of brain cell excitability as a mechanism for analgesia from infused lidocaine by increasing the current threshold of rat hippocampal pyramidal cells.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, in patients undergoing laparoscopic cholecystectomy, the total fentanyl consumption was found to be significantly lower in the lidocaine group (242 ± 48.5 µg vs 323 ± 70.8 µg) [32]. It should be pointed out the evidence for an opioid sparing effect of systemic lidocaine is not consistently clear in the published clinical literature regardless of whether lidocaine is used with volatile or intravenous anesthesia [11,22,23,25,30,33]. However, the evidence is strong in support of the effect of systemic lidocaine in reducing the total dose of volatile anesthetic required for general anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18] Other mechanisms of action influencing neuronal transmission include inhibition of G-protein coupled receptor and N-methyl-D-aspartate receptors. 19 Epidural lidocaine administration has been used commonly during obstetric procedures to provide spinal anesthesia by causing sensory and motor block. 16 Lidocaine in CSF was not measured in our study, but its concentration is presumed to be high because of its route of administration.…”
Section: Discussionmentioning
confidence: 99%
“…It has been demonstrated that lidocaine infusion accelerates bowel movements, reduces postoperative pain and opioid needs and length of hospital stay [2][3][4]. Anti-inflammatory, analgesic and antihyperalgesic effects have been implicated in lidocaine's clinical effects via different mechanisms including sodium channel blockade [6] and inhibition of G proteincoupled receptor [7].…”
Section: Introductionmentioning
confidence: 99%
“…In the last years, numerous studies have focused on the effects of lidocaine infusion on postoperative pain, recovery and short term outcome [1][2][3][4][5]. It has been demonstrated that lidocaine infusion accelerates bowel movements, reduces postoperative pain and opioid needs and length of hospital stay [2][3][4].…”
Section: Introductionmentioning
confidence: 99%